Evaluating Conservation Effectiveness of Nature Reserves Established for Surrogate Species：Case of a Giant Panda Nature Reserve in Qinling Mountains,China - Xu, Weihua; Viña, Andrés; Qi, Zengxiang; Ouyang, Zhiyun; Liu, Jianguo; Liu, Wei; Wan, Hui (Chinese geographical science, 2014)
Many nature reserves are established to protect the habitat needs of particular endangered species of interest but their effectiveness for protecting other species is questionable. In this study, this effectiveness was evaluated in a nature reserve network located in the Qinling Mountains, Shaanxi Province, China. The network of reserves was established mainly for the conservation of the giant panda, a species considered as a surrogate for the conservation of many other endangered species in the region. The habitat suitability of nine protected species, including the giant panda, was modeled by using Maximum Entropy (MAXENT) and their spatial congruence was analyzed. Habitat suitability of these species was also overlapped with nature reserve boundaries and their management zones (i.e., core, buffer and experimental zones). Results show that in general the habitat of the giant panda constitutes a reasonable surrogate of the habitat of other protected species, and giant panda reserves protect a relatively high proportion of the habitat of other protected species. Therefore, giant panda habitat conservation also allows the conservation of the habitat of other protected species in the region. However, a large area of suitable habitat was excluded from the nature reserve network. In addition, four species exhibited a low proportion of highly suitable habitat inside the core zones of nature reserves. It suggests that a high proportion of suitable habitat of protected species not targeted for conservation is located in the experimental and buffer zones, thus, is being affected by human activities. To increase their conservation effectiveness, nature reserves and their management zones need to be re-examined in order to include suitable habitat of more endangered species. The procedures described in this study can be easily implemented for the conservation of many endangered species not only in China but in many other parts of the world.